2008
DOI: 10.1002/art.23339
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life over time in patients with systemic lupus erythematosus

Abstract: Objective. To determine whether quality of life in patients with systemic lupus erythematosus (SLE) measured by the Short Form 36 (SF-36) changes over time and which patient-and disease-related factors influence such change. Methods. SLE patients who had >6 SF-36 evaluations during followup were identified from a database. Outcomes were slopes of scores of the 8 SF-36 domains as well as the physical and mental component scores. Based on the direction of the slope, patients were designated as unchanged, improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
112
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 20 publications
15
112
1
4
Order By: Relevance
“…Whether SF-36 is responsive to change is still in question. It has been shown previously that in SLE patients with established disease, the SF-36 changes little over an 8-year period (17). Changes in the SF-36 are not affected by cumulative disease activity, steroid use, or damage accumulation during the interval, but are affected by the presence of fibromyalgia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Whether SF-36 is responsive to change is still in question. It has been shown previously that in SLE patients with established disease, the SF-36 changes little over an 8-year period (17). Changes in the SF-36 are not affected by cumulative disease activity, steroid use, or damage accumulation during the interval, but are affected by the presence of fibromyalgia.…”
Section: Discussionmentioning
confidence: 82%
“…Once the disease was stabilized at years 2-5, the SF-36 remained unchanged. Although we did not test this within this study, this hypothesis is supported by the studies that showed improvement in the SF-36 in clinical trials (18,19,21), but no change in studies with prevalent patients late in the course of disease (17). We also did not include fibromyalgia in the current models, since this item is not collected in the SLICC database.…”
Section: Discussionmentioning
confidence: 89%
“…Al respecto, los estudios no son concluyentes respecto al tiempo de diagnóstico de la enfermedad de LES, ya que hay investigaciones que demuestran que no hay cambios significativos en la CVRS en pacientes con LES evaluados durante ocho años (Kuriya, et al, 2008), mientras que otros autores plantean que los años de evolución de la enfermedad pueden afectar de manera importante la percepción de salud general de la CVRS (Freire, Maia, Nepomuceno y Ciconelli, 2007;Kulczycka, et al, 2008). Se ha visto incluso en otros tipos de enfermedades crónicas, véase hipertensión, diabetes, asma y migraña que la CVRS puede fluctuar a través del tiempo (Bazán, Osorio, Paredes y Ríos, 2003).…”
Section: Discussionunclassified
“…Others have reported that some associations in certain situations, such as a significant clinical change in disease activity and short intervals between HRQoL assessments (1, 3, and 6 months), as in RCTs (9,12,(22)(23)(24). It has also been shown that the SF-36, when used to assess HRQoL crosssectionally, reflects the presence or absence of fibromyalgia as well as disease activity (5,25,26). Clearly, several factors might affect the association between disease activity (as a construct) and HRQoL scores, and this association is often explored by researchers in their studies.…”
Section: Evaluation Of Hrqol Measures In Slementioning
confidence: 99%
“…Some are generic HRQoL measures, such as the Medical Outcomes Study Short Form 36 (SF-36) questionnaire, while others, such as the Lupus Quality of Life (LupusQoL) questionnaire, are disease-specific (2,3). The SF-36 is an internationally well-validated measure of HRQoL that has a broad scope of questions validated across different chronic diseases and comorbidities (1,(3)(4)(5)(6)(7). It was recommended by Outcome Measures in Rheumatology (OMERACT) IV for assessment in randomized controlled trials (RCTs) and longitudinal observational studies in SLE (8).…”
Section: Introductionmentioning
confidence: 99%